Pengaruh Pemberian Berbagai Konsentrasi Ekstrak Daun Sirih (piper bettle l) terhadap Kadar Protein Kasar, Air, Lemak, dan Kadar Abu Telur Itik Asin Rebus - Nurmariyantini Dewi Nurma; Mudawamah Mudawamah (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
One of the common egg preservation methods is salting. The delicious tasting characteristics and abundant availability make eggs popular among most people, but eggs are easily damaged during storage. Research on the effect of giving betel leaf extract on the chemical composition of salted eggs was conducted at the Laboratory of Animal Nutrition and Feed Science, Faculty of Animal Husbandry, University of Mataram, with the aim of determining the level of betel leaf extract that is good for making salted eggs so that the chemical composition is not reduced. The material used was 36 duck eggs obtained from duck farmers in Prapen Praya Village, Central Lombok, with an average egg weight of 68.20 grams with a coefficient of variation = 16.73%. Making salted eggs by giving betel leaf extract (25%, 50% and 75%), but there were some eggs that were not salted with betel leaf extract (Control) for observation of the chemical composition of control eggs. The chemical composition of salted eggs was observed by proximate analysis. The variables observed were water content, crude protein content, crude fat content and ash content. This research is an experimental method using Analysis of Variance (ANOVA) because to compare the amount of 4 treatments (control, 25%, 50%, 75%) the data of water content, protein, fat are ratio data (percentage numbers). Water, protein, and fat content are continuous ratio data (percentage numbers) that meet the requirements of interval/ratio data assumptions for ANOVA. The results of the study were analyzed using statistical analysis using ANOVA analysis showing that the administration of betel leaf extract as much as 25%, 50% and 75% of the egg weight in making salted eggs had no significant effect (P > 0.05) The ash content of boiled salted duck eggs with details in sequence: percentage of water content, crude protein, crude fat and ash for control eggs was 69.63%; 11.84%; 14.17%, 2.11% percentage of water, ash content, crude fat content and crude protein content for the 25% concentration of betel leaf extract was 70.04%; 70.045%, 14.36% and 11.60%. The percentage of water content, ash content, crude fat content, crude protein content with a concentration of 50% is 69.49%; 69.49%; 14.0% and 11.5%. The water content, ash content, fat content and protein content of betel leaf extract in boiled salted duck eggs with a concentration of 75% is 69.485%; 69.485%; 14.75%.